Zinc Anode for Mild Aqueous Zinc-Ion Batteries: Challenges, Strategies, and Perspectives - Yang, Jinzhang; Yin, Bosi; Sun, Ying; Pan, Hongge; Sun, Wenping; Jia, Baohua; Zhang, Siwen; Ma, Tianyi (Nano-Micro Letters, 2022)
The rapid advance of mild aqueous zinc-ion batteries (ZIBs) is driving the development of the energy storage system market. But the thorny issues of Zn anodes, mainly including dendrite growth, hydrogen evolution, and corrosion, severely reduce the performance of ZIBs. To commercialize ZIBs, researchers must overcome formidable challenges. Research about mild aqueous ZIBs is still developing. Various technical and scientific obstacles to designing Zn anodes with high stripping efficiency and long cycling life have not been resolved. Moreover, the performance of Zn anodes is a complex scientific issue determined by various parameters, most of which are often ignored, failing to achieve the maximum performance of the cell. This review proposes a comprehensive overview of existing Zn anode issues and the corresponding strategies, frontiers, and development trends to deeply comprehend the essence and inner connection of degradation mechanism and performance. First, the formation mechanism of dendrite growth, hydrogen evolution, corrosion, and their influence on the anode are analyzed. Furthermore, various strategies for constructing stable Zn anodes are summarized and discussed in detail from multiple perspectives. These strategies are mainly divided into interface modification, structural anode, alloying anode, intercalation anode, liquid electrolyte, non-liquid electrolyte, separator design, and other strategies. Finally, research directions and prospects are put forward for Zn anodes. This contribution highlights the latest developments and provides new insights into the advanced Zn anode for future research. Highlights: 1 This article mainly summarizes the challenges and the latest research progress of highly reversible zinc anodes in mild aqueous zinc-ion batteries and proposes corresponding recommendations.